The Influence of Management Information Systems, Competency and Work Discipline toward Civil Servants Performance in Cipayung District, Depok Municipality - Lia Yuliawati, Ros; Purwoko, Dwi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
The issue of subpar civil servant performance exists in Cipayung District, Depok Municipality. The study attempts to ascertain and evaluate the partial and simultaneous effects of work discipline, competency, and management information systems on the performance of civil servants in Cipayung District, Depok Municipality. This study employs an explanatory approach to quantitative research. There were 186 district and sub-district government officials in the research population; 123 samples were obtained using Stephen and Willian's sample table (standard error 5%). Multiple linear regression analysis techniques are used in the data analysis method. Research findings: (1) The Management Information System has a 55.20% partly favorable and significant influence on the performance of civil servants in Cipayung District, Depok Municipality. (2) There is a notable and perhaps beneficial influence.